Mothers' experiences of settling infants in central Vietnam "through their eyes": A photo-elicitation study. Issue 5 (4th May 2019) - Murray, Linda; McDonald, Nicole; Thang, Vo Van
Abstract: There is little research on beliefs and practices regarding unsettled infant behavior and infant sleep in low and lower-middle income countries such as Vietnam. Here, researchers used a participatory qualitative visual method (photo-elicitation) to investigate how infant settling was perceived "through the eyes" of new mothers in Central Vietnam. Four qualitative themes emerged from the data: "loneliness in the midst of the crowd", "finding the right position", "protecting from cold", and "affection and exhaustion". Further research into how parenting programs and evidence based infant sleep guidelines can be modified to be socially acceptable in Vietnam is recommended.